MANAJEMEN PROGRAM PENDIDIKAN di TVRI RIAU & KEPRI (Tinjauan Berdasarkan Fungsi Manajemen) - Debi Ramona; Isjoni Isjoni; Azhar Azhar (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
This study aims to explain the management functions of educational programs on TVRI Riau & Riau Islands Station. This type of research is qualitative research. The data type of this research is using primary data. Research data was obtained from the head of the program and business development section, head of the program subsection, and all staff of TVRI Riau & Riau Islands. The instrument of this research is the researchers themselves by applying interview guides, observation checklists, and documentation. Data analysis techniques are field analysis and results analysis, process results by (1) data reduction, (2) data presentation, (3) conclusion drawing. The results of this study indicate that the management of education programs at Tvri Riau & Riau Islands stations have met television management standards, starting from complete facilities, adequate human resources despite the limited number of human resources, having a structured organizational structure.